Peran Pemerintah Dalam Meningkatkan Volume Ekspor Kopi - Jamil, M. Nadhif Fajrul; Abdika, M. Frizki; Thaher, Yucintha Qudsi Mutiara; Wikansari, Rinandita (Journal of Economics and Management, 2023)
Indonesia is one of the largest coffee producers in the world. Of course, it has great potential to increase the performance and volume of coffee exports globally. Given that Indonesia has become one of the largest coffee producers in the world, the development of coffee production must be carried out carefully and consistently. This research is focused on discussing what efforts the government has made in increasing coffee exports to the global market and the influence of farmers in increasing the volume of coffee exports themselves. So that later it can compete with other coffee-producing countries. The development of the coffee commodity industry is an ideal situation because Indonesia has abundant natural resources and a supportive archaeological environment. This requires government participation in improving the performance of national coffee production. From the results of this study, it is known that the government continues to strive to maximize the volume of coffee exports so that it continues to increase to the world market. The government conducts coaching to farmers, markets to the global market and improves the quality and productivity of coffee.